Analysis of Goroawase on Social Media A Morphosemantic Study - Nugroho, Bagas Dwi; Masrokhah, Yuni (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
Goroawase is a Japanese word game that connects numbers to words or phrases based on sound similarities. This technique is often used to create mnemonics, codes, or hidden messages, such as in phone numbers, important dates, or popular culture terms. Goroawase has unique potential in conveying messages in a creative way, both as wordplay and as an interesting communication tool in Japanese culture. This study aims to find out how the patterns and variations of Goroawase read and to find out the relationship between the meanings of Goroawase in terms of morphosemantic studies. The research method used in this study uses descriptive method and the technique used is literature. The result of this research is a variation of On-kun combination with a total of 23 data, On-kun-ei with a total of 18 data, On-yomi with a total of 10 , On-ei with a total of 6 data, Ei-kun with a total of 2 data, and one data with a special reading method involving additional elements outside the main theory. In terms of morphological process, Goroawase is mostly formed through derivation with 32 data, while reduplication is found in 10 data, and composition in 8 data. In terms of semantic meaning relations, polysemy is the most dominant meaning relation with 47 data, while synonyms are only found in 3 data.